Gonad Maturation of Clown Loach (Botia macracanthus) in Pond - Effendi, Irzal; Prasetya, T.; Sudrajat, Agus Oman; Suhenda, N.; Sumawidjaja, K. (Indonesian Society of Scientific Aquaculture (ISSA), 2003)
The objective of this research is to know the gonad maturation of clown loach Botia macracanthus) reared in pond. Two groups contain 4 female broodstock; I) carried and II) non-carried egg broodstock were reared in two separated hapas which placed in pond. Each hapa was also stocked nine males. The fish were fed pellet (32,33% protein) 10% biomass, daily in three times. After 20 days, the broodstocks were implanted by LHRH-a 100 u.g/kg of body weight. In the group I, diameter of egg in gonad were developed from 1,028 mm at the beginning of implantation to 1,071 and 1,106 mm at day of 15 and 30 after implantation respectively. In the group II, only one female has developed her gonad successfully. The egg was developed to 0,937 and 1,026 mm after 15 and 30 day implantation respectively. Key words : Gonad maturation, clown loach, Botia macracanthus, pond ABSTRAK Penelitian ini bertujuan untuk mengetahui pematangan gonad induk ikan botia (Botia macracanthus) yang dipelihara di kolam. Dua kelompok induk betina; I) sudah mengandung telur dan II) belum mengandung telur masing-masing sebanyak 4 ekor dipelihara masing-masing dalam 2 hapa. Ke dalam setiap hapa juga ditempatkan induk jantan sebanyak 9 ekor. Induk diberi pakan berupa pelet (protein, 32,33%) sebanyak 10% dari bobot biomasa per hari, 3 kali sehari, dan diberi LHRH-a dengan dosis 100 ng/kg bobot tubuh secara implantasi pada hari ke 20 pemeliharaan. Induk dalam kelompok pertama telurnya berkembang dari rata-rata 1,028 pada saat pemberian LHRH-a menjadi rata-rata 1,071 dan 1,106 mm masing-masing pada hari ke 15 dan 30 setelah pemberian. Pada kelompok kedua hanya satu ekor induk yang berkembang gonadnya setelah diberi LHRH-a. telur induk ikan tersebut berkembang dari 0,937 menjadi 1,026 mm masing pada hari ke 15 dan 30 setelah implantasi. Kata kunci : Pematangan gonad, ikan botia, Botia macracanthus, kolam",